Anxiety and depression symptoms among pregnant women with different smoking habits - Tojal, C (2020)
Smoking during pregnancy is a major public health issue. The aim of this study isto describe the smoking habits of women during pregnancy and its association with clinically significant depressive and anxiety symptoms. 382 women answered to a socio-demographic questionnaire, the Hospital Anxiety Depression Scale (HADS) and the Edinburgh Postnatal Depression Scale (EPDS) at 33 weeks of gestation. Among pregnant woman, 284 are non-smokers, 38 are smokers and 60 quitted smoking during pregnancy. There was a significant association between maternal smoking status and marital status, education level and family income per month. Among smokers, the rate of quitters was quite similar among partnered and unpartnered women and higher in women with university degree and with higher family monthly income. There was a significant association between maternal smoking status and clinically significant anxious symptoms [χ2(2)=8.535, p=0.014]. Among mothers with non-university education, smokers are more likely to have clinically significant anxiety symptoms than quitters (53.6% vs 24.3%) while among mothers in higher income families, smokers are more likely to have clinically significant depressive symptoms than quitters (100% vs 11.1%). This study provides important data to inform effective public health strategies directed to pregnant women.